2002
DOI: 10.1038/sj.mp.4001003
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation, mutation detection, and association analysis of alternative promoters and 5′ UTRs of the human dopamine D3 receptor gene in schizophrenia

Abstract: The dopamine D 3 receptor gene (DRD3) is a candidate for a number of psychiatric conditions including schizophrenia, bipolar disorder and alcohol and drug abuse. Previous studies have reported associations between polymorphisms in DRD3 and these disorders, but these findings may have reflected linkage disequilibrium with pathogenic variants that are further upstream. We have isolated and sequenced approximately 9 kb of genomic sequence upstream of the human DRD3 translational start site. Using 5Ј RACE, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…24,25,8,9 In addition, thorough studies on the characterization, mutation detection and association analysis of alternative promoters and 5 0 UTRs of the human DRD3 gene in schizophrenia imply that neither the coding nor the regulatory region of DRD3 plays a major role in predisposition to schizophrenia. 10 On the contrary, the contribution of the A-206G transition to the development of Tardive Dyskinesia (TD) in schizophrenic patients treated with antipsychotics has been maintained unanimously. 26,27 In the present study we observed a marginally nonsignificant excess in the percentages of both homozygote genotypes in the patient group (P ¼ 0.054), although the estimation of the individual OR values of G-206/G-206 and A-206/A-206 genotypes using A-206/G-206 as a genotype baseline risk, revealed statistically significant association for the wild-type homozygotes, (P ¼ 0.016, OR ¼ 1.88, 95% CI ¼ 1.09 -3.26), indicating indirectly a higher risk of this genotype to develop schizophrenic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…24,25,8,9 In addition, thorough studies on the characterization, mutation detection and association analysis of alternative promoters and 5 0 UTRs of the human DRD3 gene in schizophrenia imply that neither the coding nor the regulatory region of DRD3 plays a major role in predisposition to schizophrenia. 10 On the contrary, the contribution of the A-206G transition to the development of Tardive Dyskinesia (TD) in schizophrenic patients treated with antipsychotics has been maintained unanimously. 26,27 In the present study we observed a marginally nonsignificant excess in the percentages of both homozygote genotypes in the patient group (P ¼ 0.054), although the estimation of the individual OR values of G-206/G-206 and A-206/A-206 genotypes using A-206/G-206 as a genotype baseline risk, revealed statistically significant association for the wild-type homozygotes, (P ¼ 0.016, OR ¼ 1.88, 95% CI ¼ 1.09 -3.26), indicating indirectly a higher risk of this genotype to develop schizophrenic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most recent report from the same group that conducted this meta-analysis and contributed to the original report on the DRD3 association, is essentially negative. Anney et al [26] examined 10 novel SNPs, including some in the promoter region of the gene, but found no evidence for associations between schizophrenia and any of these or with the Ser9Gly variant.…”
Section: Functional Candidate Genesmentioning
confidence: 98%
“…Like many other psychiatric disorders, schizophrenia is thought to involve the combined effects of multiple genetic components. 1,2 Research, such as linkage analyses and association studies, [3][4][5][6][7][8][9][10][11][12] has not yet identified definitive genes responsible for the disease.…”
mentioning
confidence: 99%